Asymptomatic, Delayed Migration of Intracoronary Stent in Pericardial Space: A Rare Phenomenon - Chakraborty, Praloy (JACC Case Rep, 2021)
Delayed perforation of the coronary artery and extraluminal migration of coronary stent is a rare phenomenon. We report a case in which the stent was documented to perforate the coronary artery at least 1 year after the intervention and migrated within the pericardium without any symptom. (Level of Difficulty: Intermediate.)